The visions of Julian of Norwich between gothic style and abstraction - Cirlot, Victoria (Revista Chilena de Literatura, 2019)
This article presents the relationship between the images that emerge from the visionary experience and the art of the time. The aim is to verify how visionary images fit in many cases the expressive forms coined by the iconographic tradition, which derives in part from the function of images in meditative and devotional practices. The visions of the recluse Julian of Norwich (c. 1342-43-1416), conform to the Gothic style, both by theme (the Passion of Christ) and by the mode of treatment, designed to provoke in the viewer / reader emotions and an intense compassionate feeling. Furthermore, this study will try to show how in the visionary experience new and unusual images can emerge that will only come to build a style or an artistic tendency centuries later.